"Create music that will open a person's heart": a perspective on emotional and social wellbeing as depicted in three films - Olivier, Antoinette (Koers, 2015)
"Create music that will open a person's heart": a perspective on emotional and social wellbeing as depicted in three filmsMusic in film is a powerful means for highlighting particular themes or messages. Furthermore, film music provides a background to what the viewer perceives in scenes or events through the experiences of the actors. Although mostly fictional, many emotions or situations depicted in films can be assimilated with the life experiences of the viewer. The three films in question in this article, As it is in Heaven, Les Choristes and Harmony show that, in facing life’s many challenges, singing as a form of music can serve as a means to express and/or attain a measure of emotional and social wellbeing. The meaning of group singing, the relationship between singing and wellbeing as well as the comments of conferences attendees and the interpretation of some lyrics are discussed in this qualitative research article. The preceding points link to the “broaden-and-build” model of positive emotions.